2014
DOI: 10.1177/0194599814520686
|View full text |Cite
|
Sign up to set email alerts
|

Head and Neck Cutaneous Squamous Cell Carcinoma Requiring Parotidectomy: Prognostic Indicators and Treatment Selection

Abstract: In this study, cervical, but not parotid, lymph node involvement was associated with poor outcomes in patients with advanced cSCC requiring a parotidectomy. In patients without evidence of cervical or parotid lymph node involvement, a neck dissection may be spared, given there is a 5% chance of occult disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
63
4
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(78 citation statements)
references
References 42 publications
7
63
4
4
Order By: Relevance
“…5,11,17 Given the increasing incidence of CSCC and the high morbidity and mortality of this disease, more data are needed to help guide adjuvant treatment recommendations to improve survival outcomes. 2,[7][8][9][10]18,19 Our In the present series, patients with tumors with PNI, increased diameter, poor differentiation, or regionally metastatic disease were more likely to undergo adjuvant therapy. Although these findings have been described as high-risk features for CSCC, only PNI and regional disease are currently recognized indications for adjuvant therapy.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…5,11,17 Given the increasing incidence of CSCC and the high morbidity and mortality of this disease, more data are needed to help guide adjuvant treatment recommendations to improve survival outcomes. 2,[7][8][9][10]18,19 Our In the present series, patients with tumors with PNI, increased diameter, poor differentiation, or regionally metastatic disease were more likely to undergo adjuvant therapy. Although these findings have been described as high-risk features for CSCC, only PNI and regional disease are currently recognized indications for adjuvant therapy.…”
Section: Discussionmentioning
confidence: 58%
“…7,9,[11][12][13][14][15][16] In advanced disease of the head and neck, factors such as immunosuppression, parotid and cervical nodal disease, and metastatic node size have also been associated with poor outcomes. 8,10,[17][18][19][20] After high-risk features have been identified, the question of which patients benefit from adjuvant therapy remains. Historically, recurrent tumors or tumors with PNI and increased diameter have been treated with postoperative radiation therapy.…”
mentioning
confidence: 99%
“…In 75% of patients, the main surgery was total primary resection with reconstruction followed by exenteration and temporalectomies, showing an aggressive presentation, similar to other developing countries 35 . Our data did not find an association between the type of primary surgery and survival, unusual since such a correlation is expected, however, there is comparable studies 34,38,39 .…”
Section: Synopsis Of New Findingssupporting
confidence: 50%
“…The incidence of parotid metastasis from CSCC is not common, occurring in 1% to 5% of all cases of CSCC in the head and neck region and regional metastasis can occur up to five years after resection of the primary 3-5 . The high-risk clinical features for parotid and neck metastasis from CSCC include size (T); depth; scalp, ear pavilion; immunosuppression; recurrence; poor differentiation and others [9][10][11][12] . Recently the immunosuppression induced by drug delivery to organ transplants patients, to those with autoimmune diseases and other clinical comorbidities (diabetes mellitus), has been recognized as an important risk factor for the development of CSCC, with growing incidence and mortality in the world 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…Sweeny et al reported on 218 patients with advanced cSCC. Only 81% of these patients had concurrent neck dissection.…”
Section: Discussionmentioning
confidence: 99%